Method validation of an Inductively Coupled Plasma Mass Spectrometry (ICP-MS) assay for the analysis of Magnesium, Copper and Zinc in RBC. (9th November 2022) - Bithi, Nazmin; Ricks, Daniel; Zuromski, Lauren M; Kish-Trier, Erik; Johnson-Davis, Kamisha L
Abstract: Background: Laboratory measurements of trace elements such as magnesium (Mg), copper (Cu) and zinc (Zn) in red blood cells (RBCs) are used to assess nutritional status and diagnose metal toxicity. The purpose of this study was to develop/validate an ICP-MS method for the quantification of these elements in RBCs. Methods: An aliquot of packed RBCs was diluted in alkaline diluent solution containing scandium ( 45 Sc) and gallium ( 71 Ga), as internal standards, 0.1% Triton X-100, 0.1% EDTA, and 1% ammonium hydroxide (NH4OH). The diluted specimen was aspirated onto an ICP-MS for quantitative analysis of   25 Mg,   63 Cu and   66 Zn. The method was validated for accuracy, precision, method comparison, linearity, analytical sensitivity, and carryover. Retrospective data was analyzed and non-parametric reference intervals (RIs) were calculated. Results: Accuracy and linearity were within the expected range of =±15% for all analytes. Within-run, between-run, and total imprecisions were =15% CV. All other validation experiments met acceptance criteria. Established RIs for Mg, Cu and Zn in RBCs are 3.6-7.5 mg/dL, 59.0-91.0 mcg/dL and 794.0-1470.0 mcg/dL, respectively. Retrospective analysis of patient data for Mg RBC displayed no statistically significant difference in mean concentrations between adults (>18+ yr) and children (0-18 yr) (p >0.05); however, there was a significant difference in Mg concentrations between males and females (p < 0.001). The mean and SD for Mg RBC concentration for females and males were 5.38 + 0.68 mg/dL (n=8451) and 5.42 + 0.68 mg/dL (n=3954) respectively. The 95% RI was 4.2-6.9 mg/dL; >99% of patient results were within the established RI. Cu RBC mean concentrations were not statistically significant between males and females (p> 0.05) and age differences were not evaluated due to the low number of pediatric patients (n=37). The mean and SD for Cu concentrations were 72.2 + 11.7 mcg/dL (n=423). The overall 95% RI was 54.3-96.3 mcg/dL; 88.9% of patient results were within the established RI. For Zn RBC, there was a statistically significant difference in mean concentrations between children and adults (p < 0.0001) and no statistically significant difference between sex (p > 0.05). The mean and SD for Zn concentrations in children were 1103.7 + 225.5 mcg/dL (n=188). The 95% RI for this subgroup was 707.3– 1547.6 mcg/dL; 87.8% of pediatric patients were within the established RI. In adults, the mean and SD for Zn concentrations were 1311.7 + 196.2 mcg/dL (n=1579). The 95% RI was 932.5 – 1718.3 mcg/dL; 83.3% of patient results were within the established RI. Conclusions: This method was validated and met criteria for clinical use to quantify three elements using ICP-MS for biological monitoring. Retrospective data analysis of patient results demonstrated that the method was suitable to assess nutritional deficiency and toxicity.